PESAN-PESAN AL-QUR’AN TENTANG KELUARGA SAMAWA - Hasiah . (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
The family is the most important part in life, because every person certainly craves a happy and harmonious family that is a family that is Sakinah, Mawaddah, Warahmah (Samawa). Samawa is a term as well as a prayer that is often spoken and expected by Muslims who have married or raised a family, of course the term sakinah, mawaddah, warahmah is not just a mere motto even in Islamic teachings this is the goal of marriage. In other words, that the sakinah, mawaddah, warahmah family is a gift from Allah SWT in the household, but about what the sakinah, mawaddah, warahmah family are like, there are still many Muslims who do not know it in detail.There are some who think that a sakinah, mawaddah, warahmah family is a family that has a lot of wealth, has a handsome husband or a beautiful beautiful wife, but many people who do not agree with this assumption. For this reason, in this paper the author tries to describe a family that is sakinah, mawaddah, warahmah from the point of view of Islam, of course through the Qur'an and sunnah which the author tries to write in the discussion below.